Novel biomarker signatures for idiopathic REM sleep behavior disorder: A proteomic and system biology approach. (30th October 2018) - Mondello, Stefania; Kobeissy, Firas; Mechref, Yehia; Zhao, Jingfu; Talih, Farid R.; Cosentino, Filomena; Antelmi, Elena; Moresco, Monica; Plazzi, Giuseppe; Ferri, Raffaele
Abstract : Objective: To perform a rigorous in-depth proteomics analysis to identify circulating biomarker signatures for idiopathic REM sleep behavior disorder (RBD), capable of providing new insights into the underlying pathogenic mechanisms and putative α-synuclein-related neurodegenerative processes. Methods: Serum samples from patients with idiopathic RBD (n = 9) and healthy controls (n = 10) were subjected to a thorough liquid chromatography–mass spectrometry (MS)/MS proteomics analysis using ultimate 3, 000 nanoLC interfaced to an ESI-orbitrap velos . Data were analyzed with a systems biology approach to identify altered pathways in RBD. Results: We identified 259 proteins, 11 of which displayed significantly altered expression level in patients with RBD as compared to controls. Significant reduction in serum levels of dopamine β-hydroxylase (DBH) and vitamin D binding protein (GC) were consistent with alterations in the norepinephrinergic (NErgic) and dopaminergic systems, respectively. Additional altered protein profiles indicated that immunity, inflammation, complement, and coagulation also play a role in RBD pathophysiology. Conclusions: Our results shed light on the protein signature profile, molecular pathways, and mechanisms involved in the pathogenesis of RBD and its clinical manifestation. This knowledge opens a new avenue towards more accurate and timely diagnosis and characterization of RBD, which might ultimately translate into new therapeutic strategies with disease-modifying effects. Further evaluation of the identified markers is required to confirm their diagnostic value and potential to guide clinical decision-making.